Analysis of the indoor thermal quality in low income Cypriot households during winter - Pignatta, Gloria; Chatzinikola, C. K.; Artopoulos, G.; Papanicolas, Costas N.; Serghides, Despina Kyprianou; Santamouris, Mattheos (My University, 2017)
The recent global financial and economic crisis is responsible for the significant decrease of heating energy consumption, especially in low income population that mostly live in non-thermally-performing houses. The decrease of the residents’ income results in lower internal temperatures, hence lower thermal levels and lower indoor environmental quality, which are responsible for health problems and inadequate quality of life for the residents. This paper deals with the problem of energy poverty. The aim is to investigate whether the economic crisis, which affects the heating energy consumption and the indoor thermal quality, has consequences on the social and health problems in low income families of the Republic of Cyprus, during the winter season. To this aim, an extensive continuous monitoring study in terms of indoor air temperatures was carried out, for one year since December 2013 in 38 low income households in Limassol and Paphos, two of the main districts of the island after the capital of Nicosia. Additionally, questionnaires regarding energy, environmental, social, and health data were designed and collected from each household. Consequently, a cluster analysis, based on the monitoring data related to the first two months of 2014 and the survey's responses, was performed. Poor households of Cyprus were found to live in low indoor thermal quality, i.e. their average indoor air temperatures (ranging from 16 to 19°C) are lower than the accepted limits of the comfort zone for the island (18–21°C in winter). However, the thermal comfort and health conditions were found between the “acceptable” and “good” levels for each cluster. Additionally, a strong correlation is detected between the average internal temperature of the dwellings and the average income of the selected families. Finally, the heating energy consumption was found to be lower than the country's average for the clusters characterized by high and partial deprivation.
Keywords: Cluster analysis; Energy poverty; In-field continuous monitoring; Indoor thermal quality; Low income households; Winter conditions